Pengaruh Pertumbuhan Ekonomi, IPM dan TPAK Terhadap Ketimpangan Pendapatan di Kabupaten/Kota Provinsi Kalimantan Selatan - Azhar, Muhammad Luthpi; Nuryadin, Muhammad Rusmin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
The objectives of this study were to examine the simultaneous effects of economic growth, HDI, and TPAK on income inequality in the regencies and cities of South Kalimantan Province for the years 2017–2021 and examine the partial effects of economic growth, HDI, and TPAK on income inequality in the regencies and cities of South Kalimantan Province for the years 2017–2021. This study employs panel data regression analysis with the fixed effect model and Eviews 10 software. It is quantitative descriptive in nature. According to the study's conclusions, TPAK and HDI each have a sizable impact. For the period of 2017–2021, only the Economic Growth variable has no discernible impact on income disparity in the Regencies/Cities of South Kalimantan Province. Furthermore, together the independent variables significantly influence income inequality.